SISTEM INFORMASI AKUNTANSI DAN OPTIMALISASI SIKLUS PEMBELIAN: KAJIAN LITERATUR TENTANG PENGENDALIAN INTERNAL - Aditya Putra Pamungkas; Felix Surya Rasendria; Adit Afrizal Fauzan; Umi Hanifah (Universitas Duta Bangsa Surakarta, 2025)
This study aims to analyze how Accounting Information Systems (AIS) play a role in optimizing the purchasing cycle through the implementation of effective internal control. Using a systematic literature review method based on various relevant studies, the results indicate that the integration of internal control within AIS has a significant impact on three main aspects: preventing procurement fraud, improving the effectiveness of the procurement process, and enhancing managerial performance. Features such as tiered authorization, audit trails, and access restrictions serve as key tools in promoting system transparency and accountability. Furthermore, consistently implemented internal control enables companies to quickly identify suspicious transactions and maintain data integrity. Therefore, AIS is not merely a financial reporting tool, but also serves as a fundamental pillar for operational control and strategic decision-making. These findings provide an important foundation for the future development of purchasing management systems and risk control strategies.